ANALISIS KEMAMPUAN BERPIKIR KRITIS PADA MATERI KESETIMBANGAN BENDA TEGAR DITINJAU DARI TIPE KEPRIBADIAN - Hidayat, Taufik; Sitompul, Stepanus Sahala; Arsyid, Syaiful B. (Universitas Tanjungpura, 2023)
Analysis of critical thinking skills on rigid body equilibrium material in terms of personality type. This study aims to determine the process of students' critical thinking skills in solving rigid body equilibrium problems in terms of extrovert and introvert personalities at SMA Negeri 2 Pontianak. This study used a survey method involving 37 students of class XI science. The instrument used in this study was a personality type questionnaire, a description test of 6 questions and interviews. The extroverted personality types of the three students (high, medium, low) cannot go through the inference stage. Introverted students are able to go through the stages of clarification, assessment, strategy and tactics and inference. So it can be concluded that the critical thinking skills of students in solving the problem of rigid body balance between extroverted and introverted personalities are different. It is hoped that this research can be considered in improving the ability of students regarding critical thinking abilities by paying attention to their personality type.Critical thinking skills